Habitat Use of Ringed Seals (Phoca hispida) in the North Water Area (North Baffin Bay) - Born, Erik W.; Teilmann, Jonas; Acquarone, Mario; Riget, Frank F. (ARCTIC, 2004)
In conjunction with the International North Water Polynya Study in Smith Sound (northern Baffin Bay) in 1997-99, we examined the area use and diving activity of 23 ringed seals (Phoca hispida) that had been equipped with satellite transmitters on the Greenland side of the North Water (NOW) area. The study covered the period 12 August 1996-30 June 1999. Contact with the seals was maintained for an average of 108 days (range: 8-332 days). Four seals emigrated from the NOW area. During all seasons, the seals that remained in the area spent about 90% of the time in coastal (< 100 m deep) waters in the eastern parts of the NOW area. The total area visited by the seals during the open-water season ranged between 10 300 km² (1996) and 18 500 km² (1998), corresponding to about 15% to 25% of the entire NOW area. In winter, the total area visited by the seals varied between 2500 km² (1996-97) and 7000 km² (1998-99), and in spring, between 800 km² (1999) and 2100 km² (1997). Individual movement was significantly greater during the open-water season than during winter and spring. Maximum dive depths recorded were over 500 m (maximum for the instrument) outside and 376 m inside the NOW, for a 96 kg male seal. Non-adult seals spent about 99% of the time in waters less than 100 m deep, and more than 92% of the time in the upper 50 m. In contrast, adults tended to spend more time at greater depths. The study indicated that (1) the ringed seals took advantage of the generally lighter ice conditions in the eastern NOW, and (2) that non-adults likely exploited ice-associated amphipods and young polar cod (Boreogadus saida), and adults, mainly older polar cod and cephalopods taken at greater depths. Conjointement avec l'étude internationale sur la polynie de l'Eau du Nord dans le détroit de Smith (partie nord de la baie de Baffin) menée de 1997 à 1999, on a examiné l'utilisation de cette zone et l'activité de plongée de 23 phoques annelés (Phoca hispida) munis d'émetteurs-satellite du côté groenlandais de la région de l'Eau du ...